A universal constitutive model for hybrid stress-strain controlled creep-fatigue deformation. (1st July 2022) - Zhang, Tianyu; Wang, Xiaowei; Zhou, Dewen; Wang, Runzi; Jiang, Yong; Zhang, Xiancheng; Gong, Jianming; Tu, Shantung
Highlights: Novel hybrid stress-strain controlled creep-fatigue interaction (HCFI) tests capable of producing large creep damage are performed. Cyclic and creep responses of HCFI tests are distinct from those of conventional creep-fatigue interaction (CCFI) tests. Self-adaptive hardening parameters and dynamic recovery factors are proposed to consider the wide range of test parameters. A universal constitutive model based on the Walker model is proposed and its robustness is verified. Abstract: On account of stress relaxation, the conventional strain-controlled creep-fatigue interaction (CCFI) tests make it difficult to obtain the creep-dominated data. To make up for this deficiency, a novel hybrid stress-strain controlled creep-fatigue interaction (HCFI) loading which is capable of controlling the ratio between fatigue damage and creep damage is developed. Besides, extensive comparisons of two CFI responses give better understanding of the newly proposed HCFI loading. Experimental results show that the cyclic creep behaviors under the two CFI loading conditions are obviously different. The creep strain for HCFI tests accelerates with cycle number and increases with test parameters significantly, while the creep strain decelerates with cycle number during CCFI loadings and it is not sensitive to dwell conditions. Besides, HCFI tests show a pronounced difference in failure life as the test parameters vary. These different phenomena challenge the current constitutive models, and thus, towards developing a simulation-based design methodology for high temperature components, a universal viscoplastic constitutive model based on Walker model is proposed, in which the self-adaptive hardening parameters and dynamic recovery factors are incorporated to capture the distinct cyclic deformation behaviors during HCFI and CCFI loadings. Good agreements between the experimental and simulated results verify the robustness of the proposed model in capturing various cyclic loadings, including strain-controlled cyclic loading (low cycle fatigue and CCFI), stress-controlled ratcheting-creep loading and HCFI loading, of P92 steel and Inconel 718 at different temperatures. Accordingly, apart from a loading profile able to generate wide ranges of CFI damage, this work also gives a universal constitutive model, which may provide a new solution for existing CFI design from loading waveforms to modeling methods. Graphical abstract: Image, graphical abstract